TRANSMISI WARISAN BUDAYA TRADISI MALABUH DI BANTARAN SUNGAI KUIN - Ahmad Sulthan Aqila; Nabila Ramadhani; Nahri Fauzan; Rosalina Rosalina (Lambung Mangkurat University, 2025)
This study explores the unique process of cultural transmission through the Malabuh tradition among the Banjar people along the Kuin River, Banjarmasin, South Kalimantan. The Malabuh ritual, which centers on offering food to a mystical crocodile spirit (gaduhan) inherited through specific family bloodlines, serves not only as a reflection of Banjar spiritual beliefs but also as a medium for passing down cultural values, history, and identity from one generation to the next. Employing a qualitative approach and thematic analysis of interviews with families maintaining this tradition, the research reveals that transmission occurs primarily via oral storytelling, direct mentoring by elders, and profound spiritual experiences, such as dreams or possessions, which signal the selection of successors. However, the study finds that modern challenges—such as urbanization, reduced dependence on river systems, and decreasing interest among the youth—threaten the continuity of this tradition. The absence of written documentation further increases the risk of this cultural knowledge being lost. These findings highlight the urgent need for collective efforts in documentation, cultural education, and youth engagement, so that the Malabuh tradition can continue to serve as a vital link to the Banjar people’s heritage in contemporary times.